Molecular and morphological variation in Terniopsis (Podostemaceae) show contrasting patterns. (2nd December 2018) - Koi, Satoshi; Won, Hyosig; Trần, Hùng; Ampornpan, La‐aw; Kato, Masahiro
Abstract : Previous molecular phylogenies of Podostemaceae have indicated relationships between genera and species that are quite different from the pattern of morphological variation, but conclusions have been hampered by too sparse sampling. Here, using new material collected in Cambodia, we compare the morphological variation of Terniopsis chanthaburiensis and T. heterostaminata in Cambodia, Laos and Thailand, and perform a phylogenetic analysis based on matK, including multiple samples of most species of the genus. In contrast to the molecular variation, the morphological variation (e.g. in the length of the shoots and pedicels) is large and continuous. The results indicate that the variation in Terniopsis chanthaburiensis and T. heterostaminata is intraspecific. In two other species pairs the morphological variation was found to be large and discontinuous, while there was little molecular difference. However, the opposite pattern was observed in other cases (e.g. Dalzellia zeylanica and Tristicha trifaria ). The variation in T. chanthaburiensis and T. heterostaminata does not appear to be correlated to variation in their habitats, which is submerged rock surfaces in rapid currents. Distributional and phylogenetic data indicate that Terniopsis diversified primarily in Laos and Thailand, then expanded into neighboring regions. A synopsis of the genus Terniopsis and its 14 species is provided.